Diversidade de Similiidae (Diptera, Nematocera) em córregos do estado de São Paulo, Brasil - Pepinelli, Mateus (2003)
With the aim to analyse the Simuliidae diversity in the State of São Paulo streams, a program of collection was done during two weather seasons (dry/2001; wet/2002) in 33 aquatic systems, including forested and open low order streams and outflow of water impoundments in 11 areas inside the Mata Atlântica and Cerrado forest. The immatures were collected manually and with the Surber sampler. Overall 26 Simuliidae species were analyzed and identified of which 8 were new occurrences to São Paulo State and 1 to Brazil. Simulium pertinax, S. incrustatum, S. perflavum, S. noguerai and S. inaequale were the most frequent species, collected in at least 30% of the water bodies. The numerical population density didn t show significant difference between the weather seasons (Kruskal-Wallis non parametric test). The relations between the taxonomic structure and the environment variables were analyzed by cluster analyses and principal components (Spearman s rank coefficent). Water velocity and streams dimensions were the main variables that explained the distribution of Simuliidae species. The anthropic impact level, as impoundment or deforestation may also influence the species distribution.